Laptop Stand: Face Tracking / Muhammad Izzudin Abdul Karim - Abdul Karim, Muhammad Izzudin (2020)
This company is a company that focus on the production of face tracking laptop stand. The goal of the company is to reduce stress and pain caused by using laptop in a very long time. This company is scheduled to start its operation on September 2020. The first product that will be launched by this company is Face Tracking Laptop stand that equipped with several technology. The company is dedicated to customer satisfaction and high product quality by using advanced technologies to ensure the product 's longevity and to create a user-friendly and detailed laptop stand. The company’s mission is to prevent backpain for laptop user when they are using the laptop in a very long time. Therefore, this product helps the user to use the laptop without to be in a same position. The user can free to move without having to stress about the position of the laptop. Besides that, this laptop stand is equipped with power bank designed for laptop. This can prevent stress of the user when their laptop ran out of batteries.